Benefit of Glycerine on Surface Hardness of Hybrid & Nanofill Resin Composite - Ferriza Tri Mardianti; Sukaton Sukaton; Galih Sampoerno (Conservative Dentistry Journal, 2021)
Background: Composite resins restoration is a treatment for tooth structure loss due to pathological conditions. Longevity of composite resins restoration can be affected by surface hardness restoration. Glycerin can increase surface hardness restoration with inhibit bond oxygen and free radicals on polymerization composite resins. Purpose: Analyze the increase surface hardness composite resins restoration after glycerin application before light-curing composite resins. Review(s): Of the six journals included in this literature review, five journals reported significant differences because of the obstacles in the polymerization process of the composite resin when composite contact with light-curing will activate the photoinitiator to produce highly reactive free radicals, free radicals will break the double chain carbon bonds of monomers and form single bonds of free radicals with monomers. Bonding of free radicals with monomers will produce polymeric bonds (degree of conversion) which affects the level of surface hardness of the filling. While one journal noted no significant difference in the surface hardness of composite resin after glycerin application. Conclusion: The use of glycerin before light-curing can increase the surface hardness composite resin restorations.